2012
DOI: 10.1186/gm363
|View full text |Cite
|
Sign up to set email alerts
|

A map of human microRNA variation uncovers unexpectedly high levels of variability

Abstract: BackgroundMicroRNAs (miRNAs) are key components of the gene regulatory network in many species. During the past few years, these regulatory elements have been shown to be involved in an increasing number and range of diseases. Consequently, the compilation of a comprehensive map of natural variability in a healthy population seems an obvious requirement for future research on miRNA-related pathologies.MethodsData on 14 populations from the 1000 Genomes Project were analyzed, along with new data extracted from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…); however, such prior efforts for noncoding RNAs have been challenging (Worth, Gong, & Blundell, ). We corroborated an earlier study of a smaller set of 729 miRNAs from 1000 Genomes Phase I dataset (Carbonell et al., ) and found that seed and mature domain variation is rare as compared to nearby regions (Figure b). Moreover, we report the largest catalog of seed and mature domain miRNA variation surpassing current datasets by many folds (Bhattacharya et al., ; Gong et al., ; Liu et al., ).…”
Section: Discussionsupporting
confidence: 91%
“…); however, such prior efforts for noncoding RNAs have been challenging (Worth, Gong, & Blundell, ). We corroborated an earlier study of a smaller set of 729 miRNAs from 1000 Genomes Phase I dataset (Carbonell et al., ) and found that seed and mature domain variation is rare as compared to nearby regions (Figure b). Moreover, we report the largest catalog of seed and mature domain miRNA variation surpassing current datasets by many folds (Bhattacharya et al., ; Gong et al., ; Liu et al., ).…”
Section: Discussionsupporting
confidence: 91%
“…[1] shows that we need to challenge some of the assumptions made about miRNAs, which would perhaps help us to understand better how miRNAs function. Certain questions arise from their results.…”
Section: Pathogenic Mutations In Mirnasmentioning
confidence: 99%
“…11,12 Up until recently, most studies on miRNAs in sarcoma have utilized frozen specimens and have used tissue obtained from different patients as normal controls. Given the variability in miRNA expression between different individuals, [15][16][17] this methodology may lead to inaccurate results. The relative stability of miRNAs in formalin-fixed paraffin-embedded (FFPE) archival tissue has made them an attractive resource for miRNA profiling studies and indeed has been shown to be comparable to fresh frozen specimens.…”
mentioning
confidence: 99%